RENTAL APPLICATION VCD / DVD RENTAL AT TALOON USING BORLAND DELPHI 7.0 - Jenri Lukman Halomoan Lumban Batu; Cut Asiana Gemawaty, Skom, MMSI (Jurnal Sistem Informasi, 2007)
Rental VCD / DVD rental business is engaged in VCD / DVD that require fast dataprocessing and accurately, in order to provide information about the administrativerecords of customer data and search data back old customers who have registered stillrequire quite a long time as well as loss of customer data because quite a lot of datastored.User application programs can deliver instant results, just in data processing tenants,safe to store the data, the data report rental VCD / DVD and rental evidence to begiven to the tenant. Program used in designing this application that is using BorlandDelphi 7.0.